2015
DOI: 10.2516/ogst/2015004
|View full text |Cite
|
Sign up to set email alerts
|

Pore Structure Characterization of Indiana Limestone and Pink Dolomite from Pore Network Reconstructions

Abstract: -Carbon sequestration in deep underground saline aquifers holds significant promise for reducing atmospheric carbon dioxide emissions (CO 2 ). However, challenges remain in predicting the long term migration of injected CO 2 . Addressing these challenges requires an understanding of pore-scale transport of CO 2 within existing brine-filled geological reservoirs. Studies on the transport of fluids through geological porous media have predominantly focused on oil-bearing formations such as sandstone. However, fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…19 The porosity of Indiana limestone typically ranges from 12 to 18%. 20,21 Regardless of those research data, the higher porosity in the carbonate reservoir rock can be distinguished easily in the lab. The inset figures in Figure 7a are photos of the cross sections of carbonate reservoir rock (left) and Indiana limestone (right), respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 The porosity of Indiana limestone typically ranges from 12 to 18%. 20,21 Regardless of those research data, the higher porosity in the carbonate reservoir rock can be distinguished easily in the lab. The inset figures in Figure 7a are photos of the cross sections of carbonate reservoir rock (left) and Indiana limestone (right), respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Alsharhan and Magara found that the carbonate reservoir rocks in the Middle East show exceptionally high porosity up to 30%, which makes the Arabian Gulf one of the most prolific oil fields in the world . The porosity of Indiana limestone typically ranges from 12 to 18%. , Regardless of those research data, the higher porosity in the carbonate reservoir rock can be distinguished easily in the lab. The inset figures in Figure a are photos of the cross sections of carbonate reservoir rock (left) and Indiana limestone (right), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In rocks, both large pores and small pores are connected with each other, and the only difference is how good the connectivity is. Diffusion coupling is a phenomenon in which fluid molecules are diffused between large and small pores, and it results in the uniformization of the T 2 spectrum [63][64][65][66]. Some scholars believe however that the diffusion coupling effect invalidates the method used to calculate the movable water saturation through the T 2cut-off value [23,25].…”
Section: Quantitative Classification Of Porementioning
confidence: 99%
“…Many carbonate systems also have a wide range of pore sizes (Youssef et al 2007;De Boever et al 2012;Freire-Gormaly et al 2015). Typically, these porous media exhibit multiple porosity and multi-modal pore size distributions, e.g.…”
Section: Introductionmentioning
confidence: 99%